Cascade model of X-ray M emission for the atoms of heavy metals - Borovoy, M.O.; Ishchenko, R.M. (Functional Materials, 2012)
Cascade model of X-ray M emission for the atoms of heavy metals is proposed that allows one to take into account the main channels of vacancy transfer from L to M electronic subshells, which are responsible for the generation of double vacancy (M₄.₅N and M₄.₅O) and triple vacancy (M₄.₅N², M₄.₅NO, and M₄.₅O²) states. The model allows to separately calculate the contributions of L and M subshells in the emission cross sections of M₅N and M₄N satellites, as well as Mα₁.₂ lines along with M₅O satellites and Mβ line with M₄O satellites. Comparison of relative emission cross sections of the main components of Mα and Mβ atomic spectra of Au with the experimental relative intensities of these components, excited by Kα₁.₂ radiation of Cu and Mo, indicates the correctness of the cascade model used.